KONSTRUKSI PEMBINGKAIAN PERATURAN DAERAH NOMOR 2 TAHUN 2010 PADA BERITA KASUS IBU SAENI VERSUS SATUAN POLISI PAMONG PRAJA DI KOMPAS.COM DAN REPUBLIKA.CO.ID - Laksmi Rachmaria; Indah Suryawati (Avant Garde, 2016)
This study aims to determine how the construction of the framing of Perda No.2 Tahun 2010 on the news carried by Kompas.com and Republika.co.id related to the case of Ibu Saeni versus Satpol PP. This study used a qualitative approach to framing analysis method Robert N. Entman. The results showed that the framing is done Kompas.com news brought into the realm of human rights. Ibu Saeni positioned as a victim, Perda No. 2 Tahun 2010 and Satpol PP as the cause of the problem. Kompas.com use moral claim form Indonesia Country pruralis with the motto Unity in Diversity, not a Muslim country. Problem resolution recommended be abolished Perda No. 2 Tahun 2010. Republika.co.id framing the case of Ibu Saeni to the moral realm. Republika.co.id positioned Perda No. 2 Tahun 2010 as well as Satpol PP as victims and the media as the cause of the problem. Moral claim form used Republika.co.id let Banten care of 'household' own party outside the province do not have to intervene. treatment recommendation) be maintained Perda No.2 Tahun 2010.